Biologi sebagai Media Pendidikan Nilai Keislaman Kajian Pedagogik Interdisipliner - Baharudin, Baharudin; Matdoan, Muhammad (Peneliti.net, 2025)
This study aims to examine biology as a medium for Islamic values education through an interdisciplinary pedagogical approach in madrasah learning contexts. Employing a qualitative case study design, the research was conducted in a Madrasah Aliyah involving biology teachers, Islamic Education teachers, and eleventh-grade students. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the Miles and Huberman interactive model. The findings reveal that the integration of Islamic values in biology learning remains partial and largely incidental, often limited to moral reinforcement rather than systematic instructional design. However, when biological concepts such as ecosystem balance and biotechnology are connected with Islamic principles like mizan, amanah, and khalifah fil ardh, students demonstrate increased ecological awareness and ethical reflection. The study highlights the importance of reconstructing biology instruction through an interdisciplinary framework that integrates cognitive, affective, and ethical dimensions. Such an approach contributes to meaningful learning by linking scientific knowledge with spiritual and moral values, thereby supporting holistic Islamic education.